Polyamic acid, polyamic acid solution, polyimide, polyimide film, laminate, flexible device, and method for producing polyimide film

JP7640245B2Active Publication Date: 2025-03-05KANEKA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020177534
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-22
Publication Date
2025-03-05
Estimated Expiration
2040-10-22

AI Technical Summary

Benefits of technology

【0015】 本発明のポリイミド膜は、熱安定性、低位相差および高透明性に優れ、フレキシブルデバイス用基板等に好適である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640245000001
    Figure 0007640245000001
Patent Text Reader

Abstract

To provide a polyimide which has high heat resistance (high glass transition temperature), low phase difference and high transparency, a polyamic acid used for formation of the polyimide, and the polyimide obtained therefrom.SOLUTION: A polyamic acid is a polyaddition reaction product of a diamine and a tetracarboxylic acid dianhydride, in which the diamine comprises 2, 2'-bis(trifluoromethyl)benzidine, the tetracarboxylic acid dianhydride comprises 3, 3',4, 4'-biphenyl tetracarboxylic acid dianhydride and 9, 9-bis(3, 4-dicarboxyphenyl)fluorene dianhydride, and an amount of 9, 9-bis(3, 4-dicarboxyphenyl)fluorene dianhydride to a total amount of the tetracarboxylic acid anhydride is 10-98 mol%. A polyimide film is obtained from the polyamic acid.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamic acid, a polyamic acid solution, a polyimide, and a polyimide film. Further, the present invention relates to a laminate and a flexible device including the polyimide film. [Background technology]

[0002] 2. Description of the Related Art In electronic devices such as displays and touch panels, there is a demand for devices to be made thinner, lighter, and more flexible, and the use of plastic film substrates instead of conventional glass substrates is being considered.

[0003] In the manufacturing process of these electronic devices, electronic elements such as thin film transistors and transparent electrodes are formed on the substrate. Since the formation of electronic elements requires high-temperature processes, the plastic film substrate must have heat resistance that can be adapted to high-temperature processes. In addition, along with the demand for thinner and more flexible electronic devices, there is also a demand for organic materials to be more transparent and have lower retardation.

[0004] Polyimides using monomers with rigid structures are known as plastic materials that are highly transparent and heat resistant, and exhibit low thermal expansion (Patent Document 1). Patent Document 2 describes that a polyimide film with high transparency and a low thermal expansion coefficient can be obtained by introducing a fluorene structure. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-046054 A [Patent Document 2] JP 2019-503412 A Summary of the Invention [Problem to be solved by the invention]

[0006] Polyimides that have been designed to have a shorter absorption wavelength and thus be transparent by molecular design have a high visible light transmittance, but when molded into a film, they have a large haze and may be less suitable as a substrate material for displays and the like. In addition, polyimides generally have a trade-off relationship between transparency and thermal expansion coefficient, and the thermal expansion coefficient tends to increase as the transparency is increased. Patent Document 2 shows an example in which the thickness retardation of polyimide is reduced to 1000 nm while maintaining the transparency by introducing a fluorene structure, but further low thermal expansion and high heat resistance are required for practical use as a substrate for flexible electronic devices. In view of the above circumstances, the present invention aims to provide a polyimide having high heat resistance (high glass transition temperature), low retardation, and high transparency, and a polyamic acid used to form the polyimide and a polyimide obtained therefrom. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have found that the above problems can be solved by the following means.

[0008] The polyamic acid of the present invention is a polyaddition reaction product of diamine and tetracarboxylic dianhydride, and contains 2,2'-bistrifluoromethylbenzidine as a diamine component, and 3,3',4,4'-biphenyltetracarboxylic dianhydride and 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride as tetracarboxylic dianhydride components. The amount of 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride relative to the total amount of tetracarboxylic dianhydride is 10 mol% or more, and is 10 mol% or more and 98 mol% or less.

[0009] The tetracarboxylic acid anhydride component may further contain pyromellitic anhydride. The amount of pyromellitic anhydride relative to the total amount of tetracarboxylic acid anhydrides is, for example, 1 mol % or more and 80 mol % or less.

[0010] A polyimide can be obtained by imidizing the above polyamic acid, that is, a polyimide which is a polycondensation reaction product of a diamine and a tetracarboxylic dianhydride, the diamine containing 2,2'-bistrifluoromethylbenzidine, the tetracarboxylic dianhydride containing 3,3',4,4'-biphenyltetracarboxylic dianhydride and 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride, and the amount of 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride relative to the total amount of the tetracarboxylic dianhydride is 10 mol% or more and 98 mol% or less.

[0011] The polyimide may further contain pyromellitic anhydride as the tetracarboxylic anhydride, and the amount of pyromellitic anhydride relative to the total amount of the tetracarboxylic anhydride may be 1 mol % or more and 80 mol % or less.

[0012] The polyimide may be formed as a polyimide film. For example, a polyamic acid solution containing polyamic acid and an organic solvent may be applied to a substrate to form a laminate having a film of polyamic acid on the substrate, and the laminate may be heated to imidize the polyamic acid to form a polyimide film. The maximum heating temperature of the laminate is preferably, for example, 380°C or higher and 500°C or lower. The heating time in this temperature range is preferably 5 minutes or higher and 60 minutes or lower. Laser irradiation may also be performed when peeling off the polyimide film from the substrate.

[0013] The polyimide film preferably has a glass transition temperature of 350° C. or higher, a thermal expansion coefficient at elevated temperatures from 100 to 350° C. of 100 ppm / K or lower, a light transmittance at a wavelength of 450 nm of 75% or higher, and a haze of 1.2% or lower.

[0014] One embodiment of the present invention is a laminate having the above-mentioned polyimide film provided on a substrate.One embodiment of the present invention is a flexible device having an electronic element on the above-mentioned polyimide film. Effect of the Invention

[0015] The polyimide film of the present invention has excellent thermal stability, low retardation and high transparency, and is suitable for use as a substrate for flexible devices, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Polyamic acid is obtained by polyaddition reaction of tetracarboxylic dianhydride and diamine, and polyimide is obtained by dehydration ring-closing reaction of polyamic acid. That is, polyimide is a polycondensation reaction product of tetracarboxylic dianhydride and diamine. The polyamic acid and polyimide of the present invention contain 2,2'-bistrifluoromethylbenzidine (hereinafter sometimes referred to as TFMB) as a diamine component, and 3,3,4,4-biphenyltetracarboxylic dianhydride (hereinafter sometimes referred to as BPDA) and 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride (hereinafter sometimes referred to as BPAF) as a tetracarboxylic dianhydride component. The polyamic acid and polyimide may further contain pyromellitic anhydride (hereinafter sometimes referred to as PMDA) as a tetracarboxylic dianhydride component.

[0017] (Tetracarboxylic dianhydride component) Polyimides containing BPDA as a tetracarboxylic dianhydride component exhibit low thermal expansion because BPDA has a rigid structure. The ratio of BPDA to the total amount (100 mol%) of the tetracarboxylic dianhydride components in the polyamic acid and polyimide is desirably 10 mol% to 90 mol%, preferably 15 mol% to 80 mol%, more preferably 20 mol% to 70 mol%, and even more preferably 20 mol% to 60 mol%.

[0018] By including PMDA in addition to BPDA as the tetracarboxylic dianhydride component, the polyimide tends to exhibit higher heat resistance and lower thermal expansion. The ratio of PMDA to the total amount of tetracarboxylic dianhydride components in polyamic acid and polyimide (100 mol%) is preferably 1 mol% or more and 80 mol% or less, more preferably 5 mol% or more and 60 mol% or less. If the ratio of PMDA is 5 mol% or more, the polyimide film tends to exhibit low thermal expansion, and if it is 60 mol% or less, the polyimide film tends to exhibit high transparency. In order to exhibit high transparency in the polyimide film, the ratio of PMDA is preferably less than the ratio of BPDA.

[0019] Since BPDA and PMDA have a rigid structure, when a polyimide film is produced from a polyamic acid containing only BPDA and PMDA as the tetracarboxylic dianhydride component, cloudiness due to crystallization and the like tends to occur. By containing BPAF in addition to BPDA (and PMDA) as the tetracarboxylic dianhydride, cloudiness tends to be suppressed, and a polyimide film with excellent transparency is obtained. The ratio of BPAF to the total amount of tetracarboxylic dianhydride components in the polyamic acid and polyimide, 10 mol% or more and 98 mol% or less, preferably 10 mol% or more and 90 mol% or less, more preferably 15 mol% or more and 80 mol% or less, and even more preferably 15 mol% or more and 60 mol% or less. If the ratio of BPAF is 10 mol% or more, crystallization of the polyimide is suppressed, and therefore cloudiness of the polyimide film tends to be suppressed. By suppressing crystallization, dimensional changes due to phase transition during heating are less likely to occur, and the thermal expansion coefficient of the polyimide film tends to be small. If the proportion of BPAF is 80 mol % or less, low thermal expansion properties can be maintained.

[0020] From the viewpoint of achieving both high transparency and low thermal expansion, the total of PMDA, BPDA and BPAF relative to the total amount of tetracarboxylic dianhydride components in the polyamic acid and polyimide (100 mol %) is preferably 90 mol % or more, more preferably 92 mol % or more, and even more preferably 95 mol % or more.

[0021] The polyamic acid and polyimide may contain a component other than PMDA, BPDA, and BPAF as the tetracarboxylic dianhydride component.Other tetracarboxylic dianhydrides include 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 9,9'-bis[4-(3,4-dicarboxyphenoxy)phenyl]furan, and the like. Fluorene dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, 2,3,5,6-pyridine tetracarboxylic dianhydride, 3,4,9,10-perylene tetracarboxylic dianhydride, 4,4'-sulfonyldiphthalic dianhydride, para-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, meta-terphenyl-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, (1S,2R,4S,5R)-cyclohexane tetracarboxylic dianhydride Anhydride (cis,cis,cis-1,2,4,5-cyclohexanetetracarboxylic dianhydride), (1S,2S,4R,5R)-cyclohexanetetracarboxylic dianhydride, (1R,2S,4S,5R)-cyclohexanetetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 5-(dioxotetrahydrofuryl-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, 4-( 2,5-dioxotetrahydrofuran-3-yl)-tetralin-1,2-dicarboxylic anhydride, tetrahydrofuran-2,3,4,5-tetracarboxylic dianhydride, bicyclo-3,3',4,4'-tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,4-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, and the like.

[0022] (Diamine component) Polyimide films containing TFMB as a diamine component tend to exhibit high transparency and a low linear expansion coefficient. From the viewpoint of achieving both high transparency and low thermal expansion, the amount of TFMB relative to the total amount of diamine components in the polyamic acid and polyimide (100 mol%) is preferably 90 mol% or more, more preferably 95 mol% or more, and even more preferably 99 mol% or more.

[0023] The polyamic acid and polyimide may contain a component other than TFMB as the diamine component. Examples of diamines other than TFMB include 4,4'-diaminobenzanilide, p-phenylenediamine, m-phenylenediamine, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 9,9'-(4-aminophenyl)fluorene, 9,9'-(4-amino-3-methylphenyl)fluorene, 1,4'-bis(4-aminophenoxy)benzene, 2,2'-bis(4-aminophenoxyphenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-methylenebis(cyclohexaneamine), 3,3-diamino-4,4-dihydroxydiphenyl sulfone, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.

[0024] When the diamine component contains a flexible diamine such as silicone diamine, the linear expansion coefficient of the polyimide film tends to be large. Therefore, the amount of the flexible diamine relative to the total amount of the diamine components in the polyamic acid and polyimide (100 mol%) is preferably 5 mol% or less, more preferably 1 mol% or less, and particularly preferably 0.5 mol% or less. From the viewpoint of reducing the thermal expansion coefficient, it is preferable that the flexible diamine is not contained.

[0025] (Polyamic acid and polyamic acid solution) The polyamic acid of the present invention can be synthesized by a known general method. For example, a polyamic acid solution can be obtained by reacting a diamine with a tetracarboxylic dianhydride in an organic solvent. The organic solvent used for the polymerization of the polyamic acid is preferably one that dissolves the tetracarboxylic dianhydride and diamine as monomer components and dissolves the polyamic acid produced by polyaddition. Examples of the organic solvent include urea-based solvents such as tetramethylurea and N,N-dimethylethylurea; sulfone-based solvents such as dimethylsulfoxide, diphenylsulfone, and tetramethylsulfone; amide-based solvents such as N,N-dimethylacetamide, N,N-dimethylformamide, N,N'-diethylacetamide, N-methyl-2-pyrrolidone, and hexamethylphosphoric acid triamide; ester-based solvents such as γ-butyrolactone; halogenated alkyl solvents such as chloroform and methylene chloride; aromatic hydrocarbon-based solvents such as benzene and toluene; phenol-based solvents such as phenol and cresol; ketone-based solvents such as cyclopentanone; and ether-based solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, and p-cresol methyl ether. Usually, these solvents are used alone, but two or more of them may be used in appropriate combination as necessary. In order to enhance the solubility and reactivity of the polyamic acid, the organic solvent is preferably selected from the group consisting of amide solvents, ketone solvents, ester solvents, and ether solvents, and in particular, amide solvents such as N,N-dimethylacetamide, N,N-dimethylformamide, N,N'-diethylacetamide, and N-methyl-2-pyrrolidone are preferred.

[0026] The molecular weight of the polyamic acid can be adjusted by adjusting the ratio of the molar amount of the total diamine component to the molar amount of the total tetracarboxylic dianhydride component. The monomer components used in the synthesis of the polyamic acid may contain other monomers than the diamine and tetracarboxylic dianhydride. For example, a monofunctional amine or a monofunctional acid anhydride may be used for the purpose of adjusting the molecular weight.

[0027] The synthesis of polyamic acid by polyaddition of diamine and tetracarboxylic dianhydride is preferably carried out in an inert atmosphere such as argon or nitrogen. In an inert atmosphere, the diamine and tetracarboxylic dianhydride are dissolved in an organic solvent and mixed to proceed polymerization. The order of addition of the diamine and tetracarboxylic dianhydride is not particularly limited. For example, the diamine may be dissolved or dispersed in a slurry in an organic solvent to prepare a diamine solution, and the tetracarboxylic dianhydride may be added to the diamine solution. The tetracarboxylic dianhydride may be added in a solid state, or may be added in a state dissolved in an organic solvent or dispersed in a slurry.

[0028] The reaction temperature conditions are not particularly limited. From the viewpoint of suppressing a decrease in the molecular weight of the polyamic acid due to depolymerization, the reaction temperature is preferably 80° C. or less. From the viewpoint of allowing the polymerization reaction to proceed appropriately, the reaction temperature is more preferably 0 to 50° C. The reaction time may be set arbitrarily within the range of 10 minutes to 30 hours.

[0029] A polyamic acid solution is obtained by reacting a diamine with a tetracarboxylic dianhydride in an organic solvent. A solvent may be added to the polyamic acid solution to adjust the concentration of the polyamic acid (solid content concentration of the solution). The polyamic acid solution may contain an additive for the purpose of promoting imidization by dehydration ring closure of the polyamic acid, or improving the storage stability (pot life) of the solution by suppressing imidization.

[0030] In order to impart processing properties and various functionalities to the polyamic acid and polyimide, various organic or inorganic low-molecular or high-molecular compounds may be blended. For example, the polyamic acid solution may contain dyes, surfactants, leveling agents, plasticizers, fine particles, sensitizers, silane coupling agents, etc. The fine particles may be either organic fine particles or inorganic fine particles, and may have a porous or hollow structure.

[0031] By adding a silane coupling agent to the polyamic acid solution, the adhesion between the coating film of the polyamic acid and the polyimide film formed by dehydration ring closure and the substrate tends to be improved. The amount of the silane coupling agent is preferably 1.0 part by weight or less, more preferably 0.5 parts by weight or less, and even more preferably 0.1 parts by weight or less, based on 100 parts by weight of the polyamic acid. When the silane coupling agent is added for the purpose of improving the adhesion to the substrate, the amount may be 0.01 parts by weight or more based on 100 parts by weight of the polyamic acid. The silane coupling agent may be added to the polyamic acid solution, or may be added to the solution before or during the polymerization reaction of the polyamic acid. For example, by using a silane coupling agent having an amino group, a structure derived from the silane coupling agent can be introduced to the end of the polyamic acid. When a silane coupling agent having an amino group is added to the polymerization system of polyamic acid, in order to maintain a high molecular weight of the polyamic acid, it is preferable to set the mixing ratio of the silane coupling agent to 100 parts by weight of polyamic acid (total of tetracarboxylic dianhydride and diamine) to 1.0 part by weight or less.

[0032] (Polyimide and polyimide films) The polyamic acid and polyamic acid solution may be used as they are as materials for producing products or components, or may be mixed with binder resins, additives, etc. to prepare a resin composition. Since the polyamic acid has excellent heat resistance and mechanical properties, it is preferable to imidize the polyamic acid by dehydration ring closure and use it as a polyimide. The dehydration ring closure is performed by an azeotropic method using an azeotropic solvent, a thermal method, or a chemical method. When imidization is performed in a solution state, it is preferable to add an imidizing agent and / or a dehydration catalyst to the polyamic acid solution to perform chemical imidization. When the solvent is removed from the polyamic acid solution to form a film-like polyamic acid and the film-like polyamic acid is imidized, thermal imidization is preferable. For example, a polyamic acid solution may be applied to a film substrate such as glass, a silicon wafer, a metal plate such as a copper plate or an aluminum plate, or a film substrate such as PET (polyethylene terephthalate) to form a coating film, and then heat treatment may be performed.

[0033] The polyamic acid solution can be applied to the substrate by a known method such as gravure coating, spin coating, silk screen, dip coating, bar coating, knife coating, roll coating, die coating, etc. The heating temperature and heating time during imidization may be appropriately determined. The heating temperature is, for example, within the range of 80°C to 500°C.

[0034] The polyimide of the present invention is excellent in transparency and thermal dimensional stability, and therefore can be used as a transparent substrate to replace glass, and is expected to be used in TFT substrate materials, transparent electrode substrate materials, printed matter, color filters, flexible display members, anti-reflection films, holograms, building materials, structures, etc. In particular, the polyimide film of the present invention is excellent in thermal dimensional stability, and therefore is suitably used as a transparent substrate for electronic devices such as TFT substrates and electrode substrates. Examples of electronic devices include image display devices such as liquid crystal displays, organic EL and electronic paper, touch panels, solar cells, etc. In these applications, the thickness of the polyimide film is about 1 to 200 μm, and preferably about 5 to 100 μm.

[0035] In the manufacturing process of electronic devices, electronic elements such as thin film transistors and transparent electrodes are provided on a substrate. The process of forming elements on a film substrate is divided into a batch type and a roll-to-roll type. In the roll-to-roll process, electronic elements are sequentially provided on a long film substrate while the film substrate is being transported. In the batch process, a film substrate is formed on a rigid substrate such as alkali-free glass to form a laminate, and electronic elements are provided on the film substrate of the laminate, after which the substrate is peeled off from the film substrate. The polyimide film of the present invention can be applied to either process. The batch process is advantageous in terms of cost because it can utilize the current equipment for glass substrates. An example of a method for manufacturing a polyimide film via a laminate in which a polyimide film is provided on a glass substrate is described below.

[0036] First, a polyamic acid solution is applied to a substrate to form a coating film of the polyamic acid solution, and the substrate and coating film are heated at a temperature of 40 to 200°C for 3 to 120 minutes to dry the solvent and obtain a polyamic acid film. For example, drying may be performed at two or more set temperatures, such as 50°C for 30 minutes and then 100°C for 30 minutes. The substrate and polyamic acid film laminate are heated to imidize the polyamic acid by dehydration ring closure. Heating for imidization is performed at a temperature of, for example, 200 to 500°C, and the heating time is, for example, 3 to 300 minutes. Heating for imidization is preferably performed by gradually increasing the temperature from a low temperature to the maximum temperature. The heating rate is preferably 2 to 10°C / min, more preferably 4 to 10°C / min. The maximum heating temperature is preferably 380 to 500°C, more preferably 400 to 480°C. If the maximum heating temperature is 380°C or higher, the imidization proceeds sufficiently, and a polyimide film that can be applied to high-temperature processes is obtained. If the maximum heating temperature is 500° C. or less, thermal degradation and coloration of the polyimide can be suppressed. The heating time at the maximum temperature is, for example, 5 minutes or more, and the heating time at a temperature of 380° C. or more is preferably 5 to 60 minutes. Any temperature may be held for any time until the maximum heating temperature is reached.

[0037] The imidization may be carried out under air, under reduced pressure, or in an inert gas such as nitrogen. In order to obtain a polyimide film with high transparency, heating under reduced pressure or in an inert gas such as nitrogen is preferred. As a heating device, a known device such as a hot air oven, an infrared oven, a vacuum oven, an inert oven, or a hot plate is used. In order to shorten the heating time or to express characteristics, a polyamic acid solution to which an imidization agent or a dehydration catalyst has been added may be heated by the above-mentioned method to be imidized.

[0038] In a batch-type device manufacturing process, if stress remains at the interface between the substrate and the polyimide film formed on the substrate, warping may occur in the laminate of the substrate and the polyimide film, which may cause problems in the process of forming elements on the laminate. Therefore, it is preferable that the stress (internal stress) at the interface of the laminate of the substrate and the polyimide film is small. Specifically, the internal stress is preferably -30 MPa or more and 70 MPa or less, and more preferably -20 MPa or more and 65 MPa or less. The internal stress is calculated by forming a polyimide film on a glass plate and based on the change in warp (radius of curvature) of the glass plate before and after the formation of the polyimide film.

[0039] When forming electronic elements on a substrate by a batch process, it is preferable to form elements on a laminate in which a polyimide film is provided on a substrate such as glass, and then peel the substrate from the polyimide film. Elements may be formed on the polyimide film after peeling it from the substrate.

[0040] The method of peeling the polyimide film from the substrate is not particularly limited. For example, it may be peeled off by hand, or a peeling device such as a driving roll or a robot may be used. Peeling may be performed by reducing the adhesion between the substrate and the polyimide film. For example, a polyimide film may be formed on a substrate provided with a peeling layer. A silicon oxide film may be formed on a substrate having a large number of grooves, and peeling may be promoted by infiltrating an etching solution. Peeling may be performed by irradiation with laser light.

[0041] When the substrate and the polyimide are peeled off by laser irradiation, the polyimide film must absorb the laser light, so the cutoff wavelength of the polyimide film (the wavelength at which the transmittance is 0.1% or less) is required to be longer than the wavelength of the laser light used for peeling. For example, when a XeCl excimer laser with a wavelength of 308 nm is used, the cutoff wavelength of the polyimide film is preferably 310 nm or more, more preferably 320 nm or more. When a solid UV laser with a wavelength of 355 nm is used, the cutoff wavelength of the polyimide film is preferably 360 nm or more, more preferably 365 nm or more.

[0042] Generally, polyimides tend to absorb light on the short wavelength side, and when the cutoff wavelength shifts to the long wavelength side, the film may be colored yellow due to the absorption of visible light. In the polyimide of the present invention, when the ratio of PMDA in the tetracarboxylic dianhydride component is increased, the cutoff wavelength tends to shift to the long wavelength side. By including PMDA as the tetracarboxylic dianhydride component within a range where the cutoff wavelength does not reach the visible light region, it is possible to provide the polyimide with ultraviolet absorption properties suitable for the peeling process using a UV laser in addition to transparency and thermal dimensional stability. The cutoff wavelength of the polyimide film is preferably 390 nm or less, more preferably 385 nm or less, and even more preferably 380 nm or less.

[0043] In transparent flexible substrate applications, polyimide films are required to have high transmittance over the entire visible wavelength range. Polyimide films for transparent flexible substrates preferably have a light transmittance of 75% or more, more preferably 80% or more, at a wavelength of 450 nm. The polyimide of the present invention preferably has a light transmittance in the above range when formed into a film having a thickness of 10 μm.

[0044] The transparency of the polyimide film can also be evaluated, for example, by the total light transmittance and haze according to JIS K7105-1981. The total light transmittance of the polyimide film is preferably 80% or more, more preferably 85% or more. The light transmittance at 450 nm is preferably 75% or more, more preferably 80% or more. The haze of the polyimide film is preferably 1.2% or less, more preferably 1.0% or less, and even more preferably 0.8% or less. The polyimide of the present invention preferably has a total light transmittance and haze in the above ranges when a film having a thickness of 10 μm is formed. As described above, the haze of the polyimide film tends to be reduced by including BPAF as an anhydride component in the tetracarboxylic acid.

[0045] In order to apply to high-temperature processes, the polyimide film preferably has a high glass transition temperature. Specifically, the glass transition temperature of the polyimide film is preferably 380° C. or higher, more preferably 400° C. or higher. The glass transition temperature of the polyimide film is the temperature at which the loss tangent by dynamic viscoelasticity measurement is maximum, and is measured by the method described in the Examples below. The polyimide film preferably has a small coefficient of thermal expansion (CTE) during heating. The CTE of the polyimide film is preferably -50 to 100 ppm / K, more preferably -30 to 90 ppm / K, and particularly preferably -20 to 80 ppm / K. The CTE may be 60 ppm / K or less, 50 ppm / K or less, 40 ppm / K or less, or 30 ppm / K or less, or may be -10 ppm / K or more, or 0 ppm / K or more. CTE is the amount of distortion of a sample per unit temperature in the range of 100 to 350°C when a polyimide film is heated at a heating rate of 10°C / min, and is measured by thermomechanical analysis (TMA) using the method described in the Examples section below.

[0046] The thickness direction retardation is preferably low. The thickness direction retardation (Rth) of a polyimide film having a thickness of 10 μm at 550 nm is preferably 500 nm or less, more preferably 300 nm or less, and particularly preferably 200 nm or less. EXAMPLES

[0047] [Evaluation method] The material properties and the like were measured by the following evaluation methods.

[0048] <Internal stress> A polyimide film was formed on Corning alkali-free glass (thickness 0.7 mm, 100 mm x 100 mm) whose warpage had been measured in advance, in the same manner as in the Examples and Comparative Examples, to obtain a laminate with a 10 μm-thick polyimide film on the glass. The laminate was left to stand in a desiccator for 10 minutes, and then set in a thin film stress measurement device (manufactured by Tencor, "FLX-2320-S") to measure the warpage of the laminate in a nitrogen atmosphere at 25°C. The stress generated between the glass substrate and the polyimide film at 25°C was calculated from the warpage value.

[0049] <Light transmittance and YI of polyimide film> The light transmittance of the polyimide film in the range of 200 to 800 nm was measured using a JASCO ultraviolet-visible-near infrared spectrophotometer (V-650). The transmittance was expressed in the XYZ color system, and YI was calculated according to the method described in JIS K7373.

[0050] <Haze of polyimide film> The measurement was performed using an integrating sphere type haze meter 300A manufactured by Nippon Denshoku Industries Co., Ltd. according to the method described in JIS K7105-1981.

[0051] <Polyimide birefringence> The thickness direction retardation (Rth) value was measured at a measurement wavelength of 550 nm using a retardation meter: OPTIPRO manufactured by Shintech Co., Ltd.

[0052] <Glass transition temperature (Tg) of polyimide film> Tg was measured using Hitachi High-Tech Science's TMA / SS7100 (sample size: width 3 mm, length 10 mm, film thickness measured, cross-sectional area of ​​the film calculated), with a load of 98.0 mN, and the temperature was raised from 10°C to 450°C at 10°C / min. The inflection point of the change in the strain of the sample during the temperature rise process was taken as the glass transition temperature.

[0053] <Coefficient of thermal expansion (CTE) of polyimide film> The linear thermal expansion coefficient was measured using a Hitachi High-Tech Science TMA / SS7100 (sample size: width 3 mm, length 10 mm, film thickness was measured and the cross-sectional area of ​​the film was calculated) with a load of 29.4 mN. The sample was heated from 10°C to 400°C at 10°C / min, and then cooled at 40°C / min. The linear expansion coefficient was calculated from the change in strain of the sample per unit temperature from 100 to 350°C during cooling.

[0054] [Synthesis of polyamic acid] Polyamic acid solutions 1 to 4 were obtained according to the following Production Examples 1 to 4. The abbreviations of the reagents used in each Production Example are as follows. NMP: 1-methyl-2-pyrrolidone BPDA: 3,3'-4,4'-biphenyltetracarboxylic dianhydride PMDA: Pyromellitic dianhydride BPAF: 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride TFMB: 2,2-bis(trifluoromethyl)benzidine

[0055] Example 1 In a 1L glass separable flask equipped with a stainless steel stirrer and a nitrogen inlet tube, 425.00g of N-methyl-2-pyrrolidone (hereinafter referred to as NMP) and 39.0g of TFMB were charged and stirred to dissolve, and then 13.6g of BPDA, 11.2g of PMDA, and 11.2g of BPAF were added in order while stirring the solution, and stirred for 24 hours to obtain a polyamic acid solution. The charged concentration of the diamine component and tetracarboxylic dianhydride component in this reaction solution was 15.0% by weight based on the total amount of the reaction solution.

[0056] Example 2 The amount of diamine charged was changed to 38.9 g of TFMB, and the amounts of acid dianhydrides charged were changed to 14.4 g of BPDA, 10.6 g of PMDA, and 11.1 g of BPAF, and polymerization was carried out in the same manner as in Example 1 to obtain a polyamic acid solution.

[0057] Example 3 The amount of diamine charged was changed to 38.0 g of TFMB, and the amounts of acid dianhydrides charged were changed to 20.9 g of BPDA, 5.2 g of PMDA, and 10.9 g of BPAF, and polymerization was carried out in the same manner as in Example 1 to obtain a polyamic acid solution.

[0058] Example 4 The amount of diamine charged was changed to 39.9 g of TFMB, and the amounts of acid dianhydrides charged were changed to 7.4 g of BPDA, 16.3 g of PMDA, and 11.4 g of BPAF, and polymerization was carried out in the same manner as in Example 1 to obtain a polyamic acid solution.

[0059] Comparative Example 1 The amount of the diamine charged was changed to 37.1 g of TFMB, and the amounts of the acid dianhydrides charged were changed to 27.3 g of BPDA and 10.6 g of BPAF, and polymerization was carried out in the same manner as in Example 1 to obtain a polyamic acid solution.

[0060] Comparative Example 2 The amount of the diamine charged was changed to 41.0 g of TFMB, and the amounts of the acid dianhydrides charged were changed to 22.3 g of PMDA and 11.7 g of BPAF, and polymerization was carried out in the same manner as in Example 1 to obtain a polyamic acid solution.

[0061] [Preparation of polyimide film] Each of the polyamic acid solutions obtained in the above examples and comparative examples was diluted with NMP to a polyamic acid concentration of 10.0 wt%. A polyamic acid solution was applied to a square non-alkali glass plate (Corning Eagle XG, thickness 0.7 mm) of 150 mm x 150 mm using a spin coater so that the thickness after drying was 10 μm, and dried at 80 ° C. for 30 minutes in a hot air oven to form a polyamic acid film. After heating from 20 ° C. to 350 ° C. at 5 ° C. / min in a nitrogen atmosphere, it was held at 350 ° C. for 30 minutes, and further heated to 420 ° C. at 5 ° C. / min, and then heated at 420 ° C. for 30 minutes to perform imidization, and a laminate of a polyimide film and glass having a thickness of 10 μm was obtained. The polyimide film was peeled off from the glass substrate of the obtained laminate, and the properties were evaluated.

[0062] [Table 1]

[0063] The polyimide film of Comparative Example 1, which did not contain PMDA as a tetracarboxylic dianhydride component, had a low glass transition temperature, a large CTE, and poor thermal dimensional stability.

[0064] The polyimide film of Comparative Example 2, which did not contain BPDA as the tetracarboxylic dianhydride component, had a high YI, poor transparency, and was significantly inferior in Rth.

[0065] In Examples 1, 3, and 4, the higher the ratio of PMDA in the tetracarboxylic dianhydride, the larger the Rth tended to be. On the other hand, in Comparative Example 1, which did not contain PMDA, a significant increase in CTE and a decrease in Tg were observed compared to Examples 1 and 3. From these results, it is believed that the inclusion of BPAF, in addition to BPDA and PMDA, as the tetracarboxylic dianhydride causes changes in the intramolecular and / or intermolecular interactions of the polymer, resulting in high transparency and thermal dimensional stability.

Claims

1. A polyamic acid which is a polyaddition product of a diamine and a tetracarboxylic dianhydride, the diamine comprises 2,2'-bistrifluoromethylbenzidine and does not comprise a silicone diamine; The tetracarboxylic dianhydride includes 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic anhydride, and 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride; the amount of the 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride relative to the total amount of the tetracarboxylic dianhydride is 15 mol % or more and 60 mol % or less; The amount of the pyromellitic anhydride relative to the total amount of the tetracarboxylic dianhydride is 20 mol % or more and 40 mol % or less, the amount of the 3,3',4,4'-biphenyltetracarboxylic dianhydride relative to the total amount of the tetracarboxylic dianhydride is 20 mol % or more and 60 mol % or less; The amount of the 2,2'-bistrifluoromethylbenzidine relative to the total amount of the diamines is 90 mol % or more.

2. A polyamic acid solution comprising the polyamic acid according to claim 1 and an organic solvent.

3. A polyimide which is a polycondensation reaction product of a diamine and a tetracarboxylic dianhydride, the diamine comprises 2,2'-bistrifluoromethylbenzidine and does not comprise a silicone diamine; The tetracarboxylic dianhydride includes 3,3',4,4'-biphenyltetracarboxylic dianhydride, pyromellitic anhydride, and 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride; the amount of the 9,9'-(3,4'-dicarboxyphenyl)fluorene dianhydride relative to the total amount of the tetracarboxylic dianhydride is 15 mol % or more and 60 mol % or less; The amount of the pyromellitic anhydride relative to the total amount of the tetracarboxylic dianhydride is 20 mol % or more and 40 mol % or less, the amount of the 3,3',4,4'-biphenyltetracarboxylic dianhydride relative to the total amount of the tetracarboxylic dianhydride is 20 mol % or more and 60 mol % or less; The amount of the 2,2'-bistrifluoromethylbenzidine relative to the total amount of the diamines is 90 mol % or more.

4. A polyimide film comprising the polyimide according to claim 3 .

5. 5. The polyimide film according to claim 4, which has a glass transition temperature of 350° C. or higher and a thermal expansion coefficient at elevated temperatures from 100 to 350° C. of 100 ppm / K or lower.

6. 6. The polyimide film according to claim 4, having a light transmittance of 75% or more at a wavelength of 450 nm and a haze of 1.2% or less.

7. A laminate comprising a substrate and the polyimide film according to any one of claims 4 to 6 provided thereon.

8. A flexible device comprising an electronic element on the polyimide film according to any one of claims 4 to 6.

9. A method for producing a polyimide film, comprising applying the polyamic acid solution according to claim 2 to a substrate to form a laminate having a film of polyamic acid provided on the substrate, and heating the laminate to imidize the polyamic acid.

10. 10. The method for producing a polyimide film according to claim 9, wherein the laminate is heated at a maximum temperature in the range of 380° C. to 500° C. for 5 minutes to 60 minutes.

11. A method for producing a polyimide film, comprising forming a polyimide film by the method according to claim 9 or 10, and peeling the polyimide film from the substrate.

12. The method for producing a polyimide film according to claim 11, wherein the substrate and the polyimide film are peeled off by laser irradiation.

Citation Information

Patent Citations

  • Low tinted polyimide resin composition useful in optical application field, as well as method and composition relating to the same

    JP2007046054A

  • Polyimide precursor solution and method for producing the same

    JP2019503412A

  • Polyimide precursor resin composition, polyimide resin composition, polyimide resin film, production method for layered product, production method for color filter, production method for liquid crystal element, and production method for organic el element

    WO2019065164A1

  • Polyamide acid and method for producing same, polyamide acid solution, polyimide, polyimide film, multilayer body and method for producing same, and flexible device and method for producing same

    WO2019188380A1

  • Polyamide composition, method for producing same, polyamic acid solution, polyimide, polyimide film, laminate, production method thereof, flexible device, and method for producing flexible device

    WO2020189759A1